An Apple Plus a Brazil Nut a Day Keeps the Doctors Away: Antioxidant Capacity of Foods and their Health Benefits - Kusano Bucalen Ferrari, Carlos; Percário, Sandro; Carlos Costa Baptista Silva, Jose; Aparecida Ferraz da Silva Torres, Elizabeth (Current Pharmaceutical Design, 2016)
Antioxidant-rich foods scavenge free radicals and other reactive species, decreasing the risk of different non-communicable chronic diseases. The objective of this study was to review the content of total antioxidant capacity of commonly foods comparing with experimental data and to explore the health benefits due to foods with moderate to high TAC. The TAC was analytically measured using the
Keywords: Antioxidant capacity